Impact of Inherited Foreland Relief on Retro‐Foreland Basin Architecture. Issue 3 (15th March 2023) - Gérard, Benjamin; Rouby, Delphine; Huismans, Ritske S.; Robin, Cécile; Fillon, Charlotte; Braun, Jean
Abstract: We use a Landscape Evolution Model including flexural isostasy to investigate the influence of inherited foreland relief on the stratigraphic evolution of the retro‐foreland domain during mountain building. We show models with four different types of initial relief in the foreland domain: at sea level, elevated (+300 m), a 1 km‐deep and 100 km‐wide foreland basin associated with either a forebulge at sea level or elevated at +300 m. During the first 10 Myr of simulation, the landscape evolution of the foreland is significantly altered by its inherited bathymetry/topography. The impact is then smoothed out once the foreland slope has stabilized and develops a transverse drainage network. Models record a long‐term shallowing‐up mega‐sequence driven by the increase in sediment production rate in the uplifting range and the decrease in the rate of flexural accommodation space creation in the foreland basin. The initial relief of the foreland domain alters the timing of its transition from the under‐filled to the over‐filled phase. An initially deep foreland basin is twice as thick as an initially elevated foreland. It records deep marine deposits while a foreland initially at sea level records thin shallow marine and an elevated foreland records continental deposits. The forebulge is buried by continental deposits in an initially elevated foreland while it is buried by marine sediments in other models. Alluvial fans at the foot of the range are more elevated in initially elevated forelands. We discuss our results of modeled stratigraphic architecture in comparison with the Pyrenean, Alpine and Andean retro‐foreland basins. Plain Language Summary: Rising mountain ranges locally thicken the Earth's crust and the extra load generates lateral depressions where sediments eroded in the mountain range can be stored. This process forms foreland sedimentary basins that record the growth of the mountain range. We simulated the evolution of the landscape of a mountain range to test the impact of different initial topographies of the foreland at the foot of the mountain range: low (0 m), elevated (+300 m), and deep (−1, 000 m). All models show a common evolution driven by the creation of mountain range topography and development of lateral depressions, the build‐up and connection of alluvial fans at the foot of the range followed by their progressive migration away from the range. An initially elevated foreland preserves less sediment and produces an ultimately thinner sedimentary basin than low lying or deep forelands. Erosion and sedimentation processes erase any trace of inherited relief in the landscape after ∼10–13 Myr. On the other hand, the geometry of the sediment strata in the foreland basin records the initial topography: the low and deep forelands are initially covered by marine sediments while only the initially elevated forelands are initially covered by continental sediments. Key Points: An elevated foreland domain produces a thinner flexural basin than a low foreland as more sediment is bypassed A deep foreland produces a thicker flexural basin than a low foreland because of the extra load of the inherited space filling A deep foreland is required to preserve a significant proportion of deep marine deposits in the foreland flexural basin